2019
DOI: 10.3390/agronomy9100622
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for Enhancing Legumovirus Resistance in Mungbean: Current Understanding and Future Directions

Abstract: Yellow mosaic disease (YMD) affects several types of leguminous crops, including the Vigna species, which comprises a number of commercially important pulse crops. YMD is characterized by the formation of a bright yellow mosaic pattern on the leaves; in severe forms, this pattern can also be seen on stems and pods. This disease leads to tremendous yield losses, even up to 100%, in addition to deterioration in seed quality. Symptoms of this disease are similar among affected plants; YMD is not limited to mungbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 114 publications
1
12
0
Order By: Relevance
“…Further, phenolic compounds are capable of increasing the anti-oxidant enzyme activities such as phenyl alanine lyases and trigger the antioxidant activities of catalase and peroxidase. Similar results were obtained in greengram varieties by Mantesh et al (2020) and Basavaraj et al (2019) in soybean by Singh et al (2019).…”
Section: Phenolic Contentsupporting
confidence: 87%
“…Further, phenolic compounds are capable of increasing the anti-oxidant enzyme activities such as phenyl alanine lyases and trigger the antioxidant activities of catalase and peroxidase. Similar results were obtained in greengram varieties by Mantesh et al (2020) and Basavaraj et al (2019) in soybean by Singh et al (2019).…”
Section: Phenolic Contentsupporting
confidence: 87%
“…Sholihin et al [121] identified QTLs for RWC under drought conditions. In contrast, QTL mapping in mungbean for various resistant traits such as resistance to bruchids [122][123][124][125], powdery mildew [126,127], mungbean yellow mosaic virus [128], mungbean yellow mosaic India virus [123,[129][130][131] and Cercospora leaf spot [132], have been worked out which indicates the efficiency and importance of mapping approach. Despite several studies carried out for biotic stresses, limited information is available for abiotic stress tolerance in the mungbean, therefore requiring more focus.…”
Section: Multi-omics Approaches To Understanding Drought Tolerance 41 Genomics Approachesmentioning
confidence: 99%
“…Ohwi & Ohashi), for instance, has been reported to exhibit complete resistance to bruchids, small beetles attacking vignas (6). The most common and widely spread disease among Vigna species, with major economic significance, is the Yellow Mosaic Disease (YMD) caused by Begomoviruses (19). Significant evidences were reported on the high degree of resistance of rice bean (V. umbellata) to the disease compared to other Vigna species (20,21).…”
Section: Research Articlementioning
confidence: 99%